PERANAN MAJLIS SHOLAWAT LIL HABIB JA’FAR BIN UTSMAN AL JUFRI (JMC) DALAM MEMBENTUK AKHLAK REMAJA DI DESA KAMBINGAN KECAMATAN TUMPANG KABUPATEN MALANG - Feri Kolilur Rohman; Ika Ratih Sulistiani; Nur Hasan (VICRATINA, 2019)
The world of adolescence is being engulfed in moral degeneration, both seen from morals, thinking styles, habits, ways of speaking, and daily lifestyles. The day this moral decline does not diminish even more it becomes. Real evidence can be seen when watching news on television. From the background of the research above, the researcher formulated a problem, namely about the form of the routine activities of Majlis Sholawat lil Habib Ja'far bin Utsman al Jufri (JMC) in shaping adolescent morals, what are the benefits of the routine activities of Majlis Sholawat lil Habib Ja'far bin Utsman al Jufri (JMC) for his followers especially teenagers in Kambingan Village, Tumpang District, Malang Regency, as well as what are the supporting and inhibiting factors of Majlis Sholawat lil Habib Ja'far bin Utsman al Jufri (JMC) in shaping adolescent morals in Kambingan Village, Tumpang District. The purpose of this study was to describe how the form of routine activities of Majlis Sholawat lil Habib Ja'far bin Utsman al Jufri (JMC) in shaping adolescent morals, what are the benefits of the activities of the Majlis Sholawat lil Habib Ja'far bin Utsman al Jufri (JMC) for followers, especially adolescents in Kambingan Village Overlapping Malang Regency, as well as what are the supporting and inhibiting factors of Majlis Sholawat lil Habib Ja'far bin Utsman al Jufri (JMC) in forming adolescent morals in Kambingan Village, Tumpang District. To achieve this goal, research was conducted with a type of qualitative research. The procedure of data collection is carried out using observation methods, namely observations which are research activities phenomena carried out systematically, interview method is a method of collecting data using a question and answer way verbally with research sources, and documentation methods namely looking for data on things or variable in the form of the majlis schedule, as well as recording the activities of the majlis. Keywords: Majelis Sholawat, moral, teenagers